CREDIT MANAGEMENT MODEL WITH A GIVEN LOSS RATE - Elena G. Snegova (Статистика и экономика, 2016)
This article describes the credit limit model with a given loss rate. Applying this model, it is possible to increase the profitability of the bank’s product in the case of fast loans issued in the form of credit cards. Author offers a method for simulating of credit limit utilization functions. It is formulated and solved the problem of finding the optimal credit limit for the borrower.